Can the EU confront inequality in developing countries? - Mark Furness; Mario Negre (Deutsches Institut für Entwicklungspolitik (DIE), 2012)
The distribution of global income is extremely unequal. In 2011, the richest 20 per cent of the world's population controlled more than 80 per cent of the world's income, compared to less than 2 per cent for the poorest 20 per cent. In many parts of the developing world, inequality remains stubbornly high even as absolute numbers of people living in poverty fall. Studies by the World Bank, the IMF, UNDP and UNICEF have all shown that high inequality is detrimental to sustainable economic growth and long-term poverty reduction. While recent EU policy statements have recognised that inequality is a major development challenge, few concrete measures are in place for tackling it. The European Commission's October 2011 “Agenda for Change” proposed that the EU would focus on “inclusive and sustainable growth”, thereby enabling more people to benefit from wealth and job creation. But the Agenda does not grapple with the politically sensitive question of what “inclusive” actually means. In August 2012 the Commission started to answer this question with a “Communication on social protection in EU development cooperation”. This document makes some welcome suggestions, including placing social protection at the heart of dialogue with developing countries. There is no controversy about the need to equip workers with the education and skills needed to participate in a growing economy. Only a mean-spirited few would argue with the benefits of universal healthcare and social protection for improving equality of opportunity. Reducing income inequality is, however, also crucial. This raises difficult questions for EU development policy. First, should the EU devote more political and financial resources to support efforts to confront inequality in developing countries? If so, should these be primarily focussed on middle-income countries, or leastdeveloped countries as well? Second, what is the role of the state vis-à-vis the private sector? Would facilitating more private sector activity help reduce inequality? Third, what are the lessons from the EU's own experiences in promoting inclusiveness that could be translated into its international development policies? How can these lessons be offered to partners without creating an impression that the EU is lecturing them? Measures aimed at reducing income disparities should be central to any development strategy, both for middle- income countries where income is growing and for poorer countries where mechanisms for capturing and redistributing wealth are absent. In the current political climate, such progressive thinking is out of favour in most European countries. The EU is shying away from models that worked for Europe itself and have started to work in parts of Latin America. Rather, it is replicating the “growth-plus-safety nets” model, with added emphasis on the private sector. While this is an improvement on discredited “Washington Consensus” approaches, it is still predicated on the “trickle down” philosophy and does not target inequality specifically.
Keywords: 330; Armut und Ungleichheit; Deutsche + Europäische + multilaterale Entwicklungspolitik; Soziale Sicherung und Inklusion